Relationship Between Hematocrit Values and The Degree of Dengue Fever in Dengue Fever Patients at Panembahan Senopati Hospital, Bantul - Arum Nuryati; Hieronymus Rayi Prasetya; Diana Lestari (Sean Institute, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the major public health problems in Indonesia. The incidence of DHF in Bantul Regency in 2019 increased compared to 2018. In 2019 there were 1,424 cases of DHF Incident Rate (IR 1.5%), while in 2018 there were 182 cases of Incident Rate (IR 0.18%). An increase in hematocrit will be found very often in cases of shock because there will be an increase (hemoconcentration) due to an increase in blood cell levels or a decrease in blood plasma levels, for example in cases of DHF. The purpose of this study was to determine the relationship between hematocrit values ​​and the severity of DHF in DHF patients. Method:This study used a cross-sectional study design, using 127 inpatient data at Panembahan Senopati Bantul Regional Hospital with the criteria; having symptoms of Dengue Hemorrhagic Fever who were hospitalized by undergoing hematocrit examination using a hematology analyzer in 2022. The results of the analysis showed a relationship between hematocrit values ​​and the severity of DHF with a value of p = 0.14 and r = 0.13. Conclusion: There is no relationship between hematocrit values ​​and the severity of DHF in DHF patients.